Evaluating Service Computing Framework with Scrum through a Case Study - Andri Kusdiyanto; Wardani Muhamad; Suhardi Suhardi (IJAIT (International Journal of Applied Information Technology), 2023)
The Service Computing Framework with Scrum (SCFS) is a framework that combines Services Computing Systems Engineering (SCSE) with the Scrum Framework. This framework was created to produce a system with a good service concept by following the SCSE workflow in an agile manner through the application of Scrum principles. This paper will provide an overview of how to evaluate the SCFS framework using SOA and Agile principles through a case study. The research methodology used in this paper is a Design Science Research Methodology (DSRM). This research results in project evaluations using SCFS with good Service Oriented Architecture (SOA) parameter results. The SCFS framework can also be used in Agile development environments with fairly good parameters of velocity, story points, sprint burn down, release burn up, value delivered, and job satisfaction. In case studies conducted, this framework can help accelerate the release of service systems. The first release on the test only took 34 working days, 18 working days to get the second release, and 21 working days to get the third release. If done as a whole in one cycle, the service system will take approximately 73 working days to be used.